State, Family and Women’s Reproductive Agency in China - Gao, Biye (feminists@law, 2016)
This paper describes the alternative roles that patriarchal families and oppressive state policy might play in local women’s exercise of reproductive agency. Based on interviews with 26 rural women in Hunan, China, the paper explains how women, rather than experiencing their reproductive bodies as victims, act as agents. Theoretically, this paper engages with feminist discussions of coercion, victimhood, and agency. Through an examination of the different roles that marital and natal families play in women’s resistance to state violence, and how women employ state policy to resist reproductive duties within families, it extends the feminist scholarship on coercion and agency by proposing further investigation of the operation of different layers of repression and the possibility of agents’ manipulation of oppressions. Moreover, I reflect on the gender politics that underpin women’s reproductive agency and argue that gender equality and reproductive empowerment should be promoted in tandem in the Chinese context.